EFEKTIVITAS PEMBELAJARAN DARING SELAMA MASA PANDEMIC PADA MATA PELAJARAN MATEMATIKA - Yasika Egi Putri Chika (MEGA: Jurnal Pendidikan Matematika, 2022)
Abstract This study aims to determine the effectiveness of online learning during the pandemic. This research is a qualitative research with descriptive method. The subjects of this study were 5 grade IX students of SMP Negeri 24 Tangerang. The data collection technique used a questionnaire questionnaire containing questions about student responses to online learning in mathematics. Data analysis in this study used descriptive statistical analysis. The results of the study are shown from the results of the calculation of the percentage of student responses to online learning in mathematics subjects is 60% with the qualification criteria "less effective". This happens because students are not motivated to participate in online learning, and when implementing online learning in mathematics there are still many problems faced by students including not all students have cellphones to carry out online learning, limited internet quota, unstable internet network, and students find it difficult to understand the material in mathematics. So, from the various problems faced by students during online learning, this is what makes the implementation of online learning less effective. Keywords: Online Learning, Pandemic Period, and Math. Abstrak Penelitian ini bertujuan untuk mengetahui efektivitas pembelajaran daring selama masa pandemic. Penelitian ini merupakan penelitian kualitatif dengan metode deskriptif. Subjek penelitian ini adalah 5 siswa kelas IX SMP Negri 24 Tangerang. Teknik pengumpulan data menggunakan kusioner angket yang berisikan pertanyaan respon siswa terhadap pembelajaran daring pada mata pelajaran matematika. Analisis data dalam penelitian ini menggunakan analisis statistik deskriptif. Hasil Penelitian ditunjukkan dari hasil perhitungan persentase respon siswa terhadap pembelajaran daring pada mata pelajaran matematika adalah 60% dengan kriteria kualifikasiâ€œkurang efektifâ€. Hal ini terjadi karena siswa tidak termotivasi mengikuti pembelajaran daring, dan pada saat pelaksanaan pembelajaran daring pada mata pelajaran matematika masih banyak permasalahan yang dihadapi siswa diantaranya tidak semua siswa mempunyai handphone untuk melaksanakan pembelajaran daring, kuota internet yang terbatas, jaringan internet yang kurang stabil, dan siswa sulit untuk memahami materi pada mata pelajaran matematika. Maka, dari berbagai permasalahan yang dihadapi siswa selama pembelajaran daring, hal inilah yang menjadi pelaksanaan pembelajaran daring menjadi kurang efektif. Kata Kunci: Pembelajaran Daring, Masa Pandemic, Mata Pelajaran Matematika.